Inovasi Budidaya Maggot Black Soldier Fly (BSF) Dengan Penerapan Desain Kandang Proteksi Hama - Bibin, Muhammad; Haryono, Iranita; Andreani Syafaruddin, Andi Riska; Mattanete, Alifka; Ardian, Ani (Universitas Muhammadiyah Prof. DR. Hamka (UHAMKA Press), 2024)
Background: The use of maggot as feed in fish farming has been developed by the Pokdakan Anugrah Desa Maddenra as a solution to the high cost of commercial / manufactured fish feed. However, the problem is that the maggot production produced by Pokdakan Anugrah has not been maximized because many maggots are preyed upon by natural predators such as rats, hornbill ants and poultry. So it has not been able to meet the food needs of farmed fish. This community service activity aims to increase the production of partner group maggot cultivation as an alternative feed for fish. Method: This service activity was attended by 40 participants consisting of Partner Groups (Pokdakan Anugrah), youth and the community of Maddenra Village who have fishery businesses and UMS Rappang students. The methods carried out in this activity are through socialization/counseling, plot demonstration, mentoring and evaluation. Result: The community service team of the University of Muhammadiyah Sidenreng Rappang provides alternatives and solutions to overcome problems based on media problems, cultivation containers and predators as the main enemies of maggots with an approach to pest protection cage design. This design approach is carried out to utilize minimal space but increase the number of cultivation container media vertically and pay attention to designs that can protect the cultivation from pests. Conclusion: This community service activity is very helpful for partner groups in increasing maggot production so that it can be used as an alternative feed for farmed fish.